Zia [compact disc, unabridged] - O'Dell, Scott, 1898-1989 (Brilliance Audio, 2012)
A young Indian girl, Zia, caught between the traditional world of her mother and the present world of the Mission, is helped by her aunt Karana whose story was told in the Island of the Blue Dolphins.